2009
DOI: 10.1007/s10228-009-0116-z
|View full text |Cite
|
Sign up to set email alerts
|

Breeding season, spawning time, and description of spawning behaviour in the Japanese ornate dragonet, Callionymus ornatipinnis: a preliminary field study at the northern limit of its range

Abstract: The reproductive behaviour of the Japanese ornate dragonet (Callionymus ornatipinnis) was studied at the northernmost limit of its distribution at Usujiri in southern Hokkaido, Japan. Field observations confirmed that C. ornatipinnis reproduced at Usujiri, and this is the first detailed description of the reproductive behaviour of C. ornatipinnis. Males were observed to swim continuously in a sandy area where females were abundant, persistently approaching females and performing courtship displays. Courtship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Dragonets are also known to be highly social; however, their interactions and displays have only occasionally been investigated and mostly only in intraspecific terms (see Awata et al., 2010; Harrington, 1997; Zaiser & Fricke, 1985). In a detailed behaviour study, Harrington (1997) found that a spotted dragonet, Diplogrammus pauciradiarus (sometimes Chalinops pauciradiatus (Gill 1865)) used dorsal fin display in male–male contests, and in male–female signalling including courtship, but did not signal to two common sympatric goby species, despite the gobies displaying fins to the dragonets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dragonets are also known to be highly social; however, their interactions and displays have only occasionally been investigated and mostly only in intraspecific terms (see Awata et al., 2010; Harrington, 1997; Zaiser & Fricke, 1985). In a detailed behaviour study, Harrington (1997) found that a spotted dragonet, Diplogrammus pauciradiarus (sometimes Chalinops pauciradiatus (Gill 1865)) used dorsal fin display in male–male contests, and in male–female signalling including courtship, but did not signal to two common sympatric goby species, despite the gobies displaying fins to the dragonets.…”
Section: Discussionmentioning
confidence: 99%
“…Adult dragonets, and the males especially, are vulnerable to predators as a function of morphology and heightened activity during the breeding season and both sexes are vulnerable during vertical spawning ascents (e.g. Awata et al., 2010; Fricke & Zaiser, 1982). Several dragonet species have spectacular colouring and ornate fin extensions perhaps most notably in the form of hyperdeveloped dorsal sails (Fricke, 1982; Fricke et al., 2014; Harrington, 1997; Swainston, 2010; Thresher, 1984).…”
mentioning
confidence: 99%
“…Dragonets are gonochoristic batch spawners (Breder & Rosen 1966), and fertilization is external in 3 studied species, Callionymus maculatus Rafines que, 1810, C. ornatipinnis Regan, 1905, andBathycallionymus kaianus (Günther, 1880) (Johnson 1973, Ikejima & Shimizu 1999, Awata et al 2010. It is most likely similar in C. filamentosus.…”
Section: Discussionmentioning
confidence: 99%